Contextualizing English Language Learning: Islamic Stories as Teaching Materials in ELT - Maesaroh, Dwi Titi; Susilo, Susilo; Aridah, Aridah; Iswari, Weningtyas Parama; Asih, Yuni Utami; Suhatmady, Bibit (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
Driven by the growing awareness of cultural relevance in English language teaching (ELT), this study presents the development of English materials based on Islamic stories for Islamic schools. This study aims to describe the design of English teaching materials that integrate Islamic values in response to the lack of culturally appropriate resources available to teachers in Islamic educational settings. This study used a qualitative approach to describe the process of developing teaching materials from Islamic stories through the development stages. The primary data consists of drafts of teaching materials at each development stage, from initial design through revisions to the final prototype. Supporting data is obtained from literature, learning theories, and teaching materials design principles, which serve as the foundation for each development step. The development process involved determining learning goals, selecting and adapting content, texts, and tasks, instructions, and learning outcomes assessment. The materials were carefully designed to meet students’ linguistic level and moral development goals. In the process, the researchers do self-evaluation, consultation with experts, and revision to produce high-quality materials. This study highlights the broader framework of Islamization of knowledge in ELT, emphasizing the importance of aligning language learning with Islamic worldviews. By offering culturally and spiritually relevant learning resources, the materials developed in this study provide English teachers with practical tools to foster both language proficiency and religious character education in Muslim learners.